Visualizing digital discourse interactional, institutional and ideological perspectives - Thurlow, Crispin; Dürscheid, Christa; Diémoz, Federica (Language and social life (Mouton de Gruyter) ;, 2020)
The first dedicated volume of its kind, Visualizing Digital Discourse brings together sociolinguists and discourse analysts examining the role of visual communication in digital media. The volume showcases work from leading, established and emerging scholars from across Europe, covering a diverse range of digital media platforms such as messaging, video-chat, gaming and wikis; visual modalities such as emojis, video and layout; methodologies like discourse analysis, ethnography and conversation analysis; as well as data from different languages. With an opening chapter by Rodney Jones, the volume is organized into three parts: Besides Words and Writing, The Social Life of Images, and Designing Multimodal Texts. From the perspective of these broad domains, chapters tackle some of the major ideological, interactional and institutional implications of visuality for digital discourse studies. The first part, beginning with a co-authored chapter by Crispin Thurlow, focuses on micro-level visual practices and their macro-level framing - all with particular regard for emojis. The second part, beginning with a chapter from Sirpa Leppänen, examines the ways visual resources are used for managing personal relations, and the wider cultural politics of visual representation in these practices. The third part, beginning with a chapter by Hartmut Stöckl, considers organizational contexts where users deploy visual resources for more transactional, often commercial ends.